3444 Development of human engineered cardiac tissue (hECT)-based screening assay to explore cardiac contractile properties in response to pharmacological challenge with proarrhythmic drugs. (27th March 2019) - Stillitano, Francesca; Turnbull, Irene C.; Dave, Jaydev; Hulot, Jean-Sébastien; Hajjar, Roger J.
Abstract : OBJECTIVES/SPECIFIC AIMS: The goals of this study were (1) to evaluate the effect of proarrhythmic drugs on calcium transient and (2) to use three-dimensional human engineered cardiac tissue (hECT) technology to evaluate cardiac contractile properties in response to pharmacological challenge with proarrhythmic drugs. METHODS/STUDY POPULATION: Calcium transient was measured in subject-specific iPSC-CMs by using the IonOptix system in Sotalol treated vs. untreated conditions. We fabricated human engineered cardiac tissues (hECT) in a custom designed bioreactor using low- and high-sentitive subject-specific iPSC-CMs. Contractile function of the hECT was evaluated at baseline and after Sotalol [300 µM] administration. The change in beat rate was recorded under spontaneous beating conditions; changes in other twitch parameters, including time to relaxation, were recorded under electrical stimulation. Time to relaxation served as an indicator of action potential duration (APD), which has a temporal correlation with the QT interval. RESULTS/ANTICIPATED RESULTS: The low-sensitive iPSC-CM showed a considerable drop in overall peak height of the calcium transient, in the presence of 100 µM Sotalol. The high-sensitive line, however, showed a more pronounced drop in peak height. Sotalol treatment also induced a more pronounced increase in the exponential decay time constant (tau) in the high-sensitive line compared to the low-sensitive line. The hECT fabricated with high sensitive hiPSC-CM showed a larger decrease in spontaneous beat rate in response to Sotalol (0.41 vs 0.23 fold decrease), with a higher increase in time to relaxation (1.8 vs 1.3 fold increase), compared to hECT from low sensitive hiPSC-CM. Moreover, while the low-sensitive hECT showed a positive correlation between time to relaxation and developed force, as expected after Sotalol stimulation; the high-sensitive hECT failed to show a positive inotropic response. DISCUSSION/SIGNIFICANCE OF IMPACT: Our findings suggest subject-specific iPSC-CMs and hECT, can be used to model functional abnormalities observed in diLQTS in response to Sotalol, and offer novel insights into human-based screening assays for toxic drug reactions. Success of this study may help identify key components underlying diLQT susceptibility to ultimately develop novel therapeutic agents.